(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
Acute kidney damage in patients after SARS-CoV2 occurs against the background of a low number and activity of CD4+ cells and a high value of CD8+, CD19+ cells, which ultimately leads to impaired regeneration of individual parts of damaged nephrons, stimulating the growth and accumulation of circulating immune complexes and changing their antigenic structure. High values of phagocytic number and index may indicate the continued destruction of the basement membranes of nephrons, which ultimately leads to a decrease in the functional volume of the kidneys with the development of chronic renal failure.